Effects of wheat intercropping on growth and occurrence of Fusarium wilt in watermelon - Lv, HuiFang; Yan, CongSheng (PeerJ, 2024)
Watermelon is commonly affected by Fusarium wilt in a monoculture cropping system. Wheat intercropping alleviates the affection of Fusarium wilt of watermelon. The objective of this study was to determine the effects of wheat and watermelon intercropping on watermelon growth and Fusarium wilt. Our results showed that wheat and watermelon intercropping promoted growth, increased chlorophyll content, and photosynthesis of watermelon. Meanwhile, wheat and watermelon intercropping inhibited watermelon Fusarium wilt occurrence, decreased spore numbers, increased root vigor, increased antioxidant enzyme activities, and decreased malondialdehyde (MDA) content in watermelon roots. Additionally, wheat and watermelon intercropping enhanced the bacterial colonies and total microbes growth in soil, decreased fungi and Fusarium oxysporum f. sp. niveum (FON) colonies, and increased soil enzyme activities in watermelon rhizosphere soil. Our results indicated that wheat and watermelon intercropping enhanced watermelon growth and decreased the incidence of Fusarium wilt in watermelon. These effects could be due to intercropping inducing physiological changes, regulating soil enzyme activities, and/or modulating soil microbial communities.
Keywords: Wheat; Watermelon; Fusarium wilt; Photosynthesis; Antioxidant enzyme; Soil enzyme; Soil microbes